2010
DOI: 10.1007/s11270-010-0350-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Carbon Tetrachloride on an Anaerobic Methanol-Degrading Microbial Community

Abstract: The evolution of microbial communities with increasing carbon tetrachloride concentrations was studied in two anaerobic columns containing sand and two different clay soils, one of which contained high levels of iron. Microbial communities were characterized through analysis of column effluents with denaturing gradient gel electrophoresis and quantitative polymerase chain reaction for archaea and eubacteria as inlet carbon tetrachloride concentrations were increased from 0.8 to 29 μM. Inhibition of microbial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…As for CF, albeit our data showed biotic degradation of CF in support of previous studies (e.g., Ciavarelli et al, 2012;Chan et al, 2012, Lee et al, 2012, Lima and Sleep, 2010, the δ 13 C of CF did not vary substantially (Figure 2). This led to the lack of isotopic fractionation, which differs from the observations of Chan et al (2012) who, in contrast to us, used CF as the only parent compound susceptible to undergo isotopic fractionation as it biodegraded.…”
Section: Figuresupporting
confidence: 92%
“…As for CF, albeit our data showed biotic degradation of CF in support of previous studies (e.g., Ciavarelli et al, 2012;Chan et al, 2012, Lee et al, 2012, Lima and Sleep, 2010, the δ 13 C of CF did not vary substantially (Figure 2). This led to the lack of isotopic fractionation, which differs from the observations of Chan et al (2012) who, in contrast to us, used CF as the only parent compound susceptible to undergo isotopic fractionation as it biodegraded.…”
Section: Figuresupporting
confidence: 92%
“…Lima and Sleep 400 (2010) reported inhibition of the microbial activity related to CT degradation by 0.2-0.4 μM of 401 CF. The authors observed a decrease in the number of bacterial species, including Acidovorax, close to those considered inhibitory in the reported study byLima and Sleep (2010), which 404 supports that the lowering of δ 13 CCT enrichment after 211 days in the CTw/oB treatment (Fig. 4052C,D) might be due to the toxic effects of CF accumulation(Fig.…”
supporting
confidence: 81%
“…In PZ-19, however, lactate was not completely consumed but, in both bioaugmentation tests, its decrease was followed by acetate and propionate production (SI section K). The inability of inoculated bacteria to efficiently degrade contaminants in these microcosms suggested that there were inhibition issues, possibly due to the presence of co-contaminants in groundwater such as CT, which is a known inhibitor of the microbial activity and CF degradation in particular (section 2.2) (da Lima and Sleep, 2010;Grostern et al, 2010;Justicia-Leon et al, 2014;Wei et al, 2016). The results obtained with the microcosms suggested that, under the studied conditions, degradation of contaminants was very slow and inefficient, but possible to some extent, which agreed with the information obtained from the isotopic field data that was discussed above.…”
Section: Sitementioning
confidence: 99%
“…In addition, it has also been reported that CT and CF inhibit their mutual biodegradation (da Lima and Sleep, 2010;Grostern et al, 2010;Justicia-Leon et al, 2014).…”
Section: Introductionmentioning
confidence: 96%